Neuropsychiatric aspects of concussion: acute and chronic sequelae - Vani Rao; Arshiya Syeda; Durga Roy; Matthew E Peters; Sandeep Vaishnavi (Concussion)
Concussion – also known as mild traumatic brain injury – is a transient disturbance of neurological function resulting from traumatic forces imparted to the brain that often produce cognitive, beha...